2007
DOI: 10.1080/10641734.2007.10505217
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Influence of Gender and Sexual Self-Schema on Affective Responses to Sexual Content in Advertising

Abstract: This investigation contributes to work on emotion-based advertising by testing responses to three types of sexual stimuli in commercials: ads featuring women, men, or both women and men. As expected, affective and attitudinal responses were most favorable to opposite-sex stimuli, followed by mixed-sex stimuli, with same-sex imagery evaluated least favorably. In addition, the relationship between Sexual Self-schema (SSS) and emotional response revealed that SSS significantly predicted females' affective reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 51 publications
3
31
0
4
Order By: Relevance
“…A key consideration here is that as Reichert, LaTour, and Kim (2007), it would be disingenuous to claim that sexual advertising is targeted equally at consumers regardless of SSS level. Rather, these advertisements are primarily targeted at high-SSS consumers (in the present study, female consumers).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key consideration here is that as Reichert, LaTour, and Kim (2007), it would be disingenuous to claim that sexual advertising is targeted equally at consumers regardless of SSS level. Rather, these advertisements are primarily targeted at high-SSS consumers (in the present study, female consumers).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike many other scales measuring sexual attitudes and/or behaviors, this scale is veiled and unobtrusive, with items that are not revealing of their true purpose, thus avoiding potential bias. The scale has exhibited strong validity and been successfully implemented in recent advertising explorations (Reichert andFosu 2005, Reichert, LaTour, andKim 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies show that the gender has a significant influence on viewers' responses to the bareness in advertisements (Dianoux & Linhart, 2010;Jeong & Hwang, 2005;Nelson & Pack, 2008;Sabri & Obermiller, 2011). The use of the opposite sex in the commercial produces a very strong result (Liu, Li, & Cheng, 2006;Reichert, LaTour, & Kim, 2007;Reichert & Fosu, 2005;Sengupta & Dahl, 2008), particularly with regard to female bareness (Jeong & Hwang, 2005). Studies conducted on the relationship between the consumers' gender and their attitudes toward the use of eroticism in advertisements state that women are more sensitive to erotic provocation (Dudley, 1999).…”
Section: The Moderating Role Of Gendermentioning
confidence: 99%
“…Provocative advertisements cause positive and negative emotions that affect the reactions of viewers (Batra & Ray, 1986;Edell & Burke, 1987). These reactions, having an influence on consumers' behaviour (Liu, Cheng, & Li, 2009;Reichert et al, 2007), are measured by the attitude toward the advertisement (Bagozzi, Gopinath, & Nyer, 1999;Brown & Stayman, 1992;Mitchell & Olson, 1981;Shimp, 1981). It is also suggested that the emotions and the attitudes of consumers affect their behaviour; particularly, when they are exposed to an advertisement (DeBarnier, 2002;Holbrook & Hirschman, 1982).…”
Section: Female Bareness and Advertising Persuasionmentioning
confidence: 99%
“…The main risk is that the sexual content in advertising, while capturing the consumer's attention, can distract him from other information that is more substantial and relevant as, for example, those related to the brand (MacInnis, Moorman & Jaworski, 1991;Cui & Yang, 2009). Doubtless the use of sexual content in advertising raises the level of attention (Belch, Holgerson, Belch & Koppman, 1981;Dudley, 1999;Reichert, Heckler & Jackson, 2001;Reichert, LaTour & Kim, 2007;Lombardot, 2007) and may help to make those messages more interesting and engaging. A few years ago, Bello, Pitts, and Etzel (1983) manipulated a famous Calvin Klein jeans commercial, in which a seductive Brooke Shields was portrayed, in order to show both the sexy version (original) and the non-sexy version of the ad.…”
Section: Use Of Sexuality In Advertisingmentioning
confidence: 99%